Analisis Risiko Bahaya Penerbangan Di Sisi Airside Sebagai Upaya Meminimalisir Risiko Kecelakaan Dengan Metode Hira Di Bandara Udara Sultan Muhammad Salahuddin Bima - Riska Riska; Adipura Danang Maulana (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Sultan Muhammad Salahuddin Airport located in Bima regency, West Nusa Tenggara is the main terminal for the people of Bima and its surroundings who travel using air services. As the main terminal for Bima people who will travel by air service, Bima Airport must have a risk management system in accordance with applicable regulations, especially in the airside area where all aircraft operational activities take place in the airside area. This study aims to determine the suitability of the safety criteria of Sultan Muhammad Salahuddin Bima Airport and the steps taken by the airport in the event of a non-conformity or an event that can be categorized as hazard identification and Risk assessment (HIRA). This study used mixed methods Data collection was carried out by observation, structured interviews and documentation. The general data in this study is primary data and secondary data. Data analysis used using qualitative and quantitative data analysis techniques. The results of this study are based on research that has been carried out based on ISO 31000 on Aviation Hazard Risk Management Analysis on the Airside Side as an effort to minimize the risk of accidents with the Hira method at Sultan Muhammad Salahuddin Airport which is carried out using stages consisting of the risk identification stage, risk analysis and risk evaluation as well as the risk treatment stage, So from the study 10 dangers and risks that are likely to occur. Of the 10 risks, there are 9 risks in the red zone (high) and 1 risk in the yellow zone (medium). Of the 10 risks, they then get treatment or control because they are in the red zone and yellow zone. Controlling the possibility of 10 existing risks, Sultan Muhammad Salahuddin Airport uses control measures in implementing measures to minimize the impact of possible risks that occur, namely avoiding and reducing risks. This is supported by risk treatment carried out by the company and adjusted to 10 risks that are likely to occur.